Performance Analysis of Nigerian Brewery Industry - Elumah, Lucas O.; Shobayo, Peter (Binus Business Review, 2018)
This research attempted to assess the financial performance of the firms in the brewery industry using financial ratios. It adopted a descriptive ex-post facto research design by using brewery firms of the Nigeria Stock Exchange (NSE) from 2011-2015. The result suggests that the brewery industry is profitable and efficient in using its asset to generate profit and return it to its shareholders. Similarly, the industry financial risk is relatively low, and manager in the industry manage their stocks efficiently. This suggests that managers of firms should endeavor to reduce the amount of debt in their capital structure and manage a reasonable amount of debt in its capital structure since a high debt implies a high financial risk.